2008
DOI: 10.4049/jimmunol.180.3.1686
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role of Sialylated O-Linked Sugar Chains in the Recognition of Mouse CD99 by Paired Ig-Like Type 2 Receptor (PILR)

Abstract: The paired Ig-like type 2 receptor (PILR), which comprises both inhibitory and activating isoforms, is well conserved among most mammalians. The inhibitory PILRα possesses an ITIM in its cytoplasmic domain, whereas the activating PILRβ does not have an ITIM but transduces activating signals by associating with the ITAM-bearing DAP12 adapter molecule. Both mouse PILRα and PILRβ recognize mouse CD99, which is broadly expressed on various cells, including lymphocytes, and is involved in the regulation of immune r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 39 publications
1
47
0
1
Order By: Relevance
“…S2) and/or the differences in glycosylation (type and/or number of glycans). It has been shown that sialylated O-linked glycans on mCD99 play an essential role in PILR␣ binding (13). hCD99 has been reported to be O-glycosylated (35), and like mCD99, it does not bear any potential N-glycosylation sites.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…S2) and/or the differences in glycosylation (type and/or number of glycans). It has been shown that sialylated O-linked glycans on mCD99 play an essential role in PILR␣ binding (13). hCD99 has been reported to be O-glycosylated (35), and like mCD99, it does not bear any potential N-glycosylation sites.…”
Section: Resultsmentioning
confidence: 99%
“…LC-MS analysis of reduced fusion proteins (with and without PNGase F and sialidase digestion) showed that hCD99-Fc carried two O-glycans and mCD99-Fc carried three O-glycans with the composition NeuAc 1-2 Hex 1 HexNAc 1 . In the case of mCD99, two adjacent O-glycosylation sites, Thr-45 and Thr-50 (NMKPT 45 PKAPT 50 PKKPS) are relevant for PILR␣ recognition (13). Sequence alignment of human and mouse CD99 showed that Thr-41 of hCD99 corresponds to the Thr-45 O-glycosylation site of mCD99 and that hCD99 lacks the second potential O-glycosylation site corresponding to Thr-50 of mCD99 (supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations